Guidance Counselors or School Counselors: How the Name of the Profession Influences Perceptions of Competence. (January 2019) - Zyromski, Brett; Hudson, Tyler D.; Baker, Emily; Granello, Darcy Haag
School counselors ( n = 276) were given a measure of school counseling competencies and standards. About half the participants completed a version of the survey that used the term "Guidance Counselor" ( n = 131) and half completed a version of the survey that used the term "School Counselor." Participants who completed the surveys that used the term "Guidance Counselor" were statistically significantly less likely to believe that school counselors were able to perform the 25 tasks on the survey.